Analisis Kepatuhan Wajib Pajak Dalam Pelaporan dan Pembayaran PPN - Chairani Pricilia; Matthew Napitupulu; Deon Hondo; Selly Stevani; Rexy Saragih (Yayasan Literasi Emas Nusantara, 2025)
This study examines taxpayer compliance in reporting and paying Value Added Tax (VAT) in Indonesia, focusing on the impact of the VAT rate increase to 12%. Taxpayer compliance levels in Indonesia remain low and fluctuate, impacting state revenue and national development. The study also analyzes factors influencing taxpayer compliance, such as awareness, understanding of regulations, the quality of service from tax authorities, and the effectiveness of the tax administration system and law enforcement. The research results are expected to provide strategic recommendations for improving VAT compliance and optimizing state revenue